Multilevel perceptions of the virtual delivery of the University of California Diabetes Prevention Program on RE-AIM domains due to COVID-19 mandates - Loeb, Tamra Burns; Gholami, Maryam; Ramm, Kate; Shedd, Kelly; Soetenga, Samantha; Jackson, Nicholas J.; Chung, Un Young Rebecca; Duru, O. Kenrik; Mangione, Carol M.; Hamilton, Alison B.; Moin, Tannaz (Frontiers in Public Health, 2024)
Background The University of California’s Diabetes Prevention Program (UC DPP) Initiative was implemented across all 10 UC campuses in 2018. The COVID-19 pandemic and accompanying mandates required swift changes to program delivery, including pivoting from in-person to virtual delivery (i.e., Zoom). Our goal was to assess multilevel constituent perceptions of the use of a virtual platform to deliver UC DPP due to COVID-19 mandates. Methods We conducted qualitative interviews with 68 UC DPP participants, coordinators, and leaders to examine the use of virtual platform delivery on the reach, effectiveness, adoption, implementation, and maintenance (RE-AIM) of UC DPP. Transcripts were analyzed using rapid qualitative analysis and emergent themes were categorized using domains corresponding to RE-AIM framework. Results Among UC DPP participants (n = 42), virtual delivery primarily impacted perceptions of UC DPP effectiveness and implementation. Some participants perceived program effectiveness to be negatively impacted, given their preference for in-person sessions, which they felt provided more engagement, peer support, and accountability. Implementation challenges included problems with virtual format (e.g., “Zoom fatigue”); however, several benefits were also noted (e.g., increased flexibility, maintenance of DPP connections during campus closures). UC DPP coordinators (n = 18) perceived virtual delivery as positively impacting UC DPP reach, since virtual platforms provided access for some who could not participate in-person, and negatively impacting effectiveness due to reduced engagement and lower peer support. UC leaders (n = 8) perceived that use of the virtual format had a positive impact on reach (e.g., increased availability, accessibility) and negatively impacted effectiveness (e.g., less intensive interactions on a virtual platform). Across constituent levels, the use of a virtual platform had little to no impact on perceptions of adoption and maintenance of UC DPP. Conclusion Perceptions of the reach, effectiveness, and implementation of UC DPP using a virtual platform varied across constituents, although all groups noted a potential negative impact on overall program effectiveness. Unanticipated program adaptations, including virtual delivery, present potential benefits as well as perceived drawbacks, primarily across the effectiveness domain. Understanding differential constituent perceptions of the impact of virtual delivery can help maximize RE-AIM and inform future UC DPP delivery strategies.